Investigation of the distribution patterns in moinids (Crustacea: Cladocera: Moinidae) forming ephippia with two resting eggs - Neretina, Anna N.; Alonso, Miguel; Kotov, Alexey A. (Zootaxa, 2024)
During last two decades, morphological and genetic studies of the microcrustaceans from the family Moinidae Goulden, 1968 (Crustacea: Branchiopoda: Cladocera) were intensified. However, species diversity within this family remains underestimated. It refers to both subtropical and tropical areas of different continents that have traditionally been less studied compared with Central Europe and some other Palaearctic regions. In addition to this, only a restricted set of morphological characteristics is used for the discrimination of species within the genus Moina Baird, 1850. Most common moinid taxa are considered species complexes rather than single species, making any biogeographic reconstruction difficult. Here, we present an investigation of distribution patterns in moinids that form ephippia with two resting eggs based on both a reexamination of data from the literature and from specimens in museum and personal collections. Also, we redescribed morphology of poorly known taxa from the arid regions of the Old World—Moina belli Gurney, 1904 and M. kaszabi Forró, 1988 and clarify their diagnostic morphological characters and distributional ranges. We found that M. belli and M. kaszabi are morphologically very similar. In both species, setae 1 and 2 of thoracic limb I are armed bilaterally by fine, densely located short setulae. Reliable differences between M. belli and M. kaszabi concern armature of the valve posteroventral portion. Among the moinids with two resting eggs in the ephippium, M. belli and M. kaszabi are morphologically closer to M. macrocopa (Straus, 1820) and M. americana Goulden, 1968. All these species have: (1) a dorsal head pore; (2) fine long hairs on head, valve and preanal margin of postabdomen; (3) thoracic limb I of male with a long exopodite. In general, an investigated group of moinids includes both species with relatively compact and very broad distributional ranges. We concluded that maximum diversity of the moinids forming ephippia with two resting eggs is characteristic of southern portions of Palaearctic and Nearctic zoogeographical regions and approximately corresponds to subtropical climate zone. We need to underline that M. macrocopa and M. americana have a great invasive potential. Both species were anthropogenically introduced in South America and have been successfully naturalized there. Their distribution in tropical regions of the Old World and Australia requires new precise investigations. A group of moinids forming ephippia with two resting eggs can be considered as a convenient model for biogeographical reconstructions, including studies on changes in aquatic ecosystems due to global climate warming, eutrophication and the introduction of non-native species. There is no doubt that subsequent joint application of morphological and genetic data will shed more light on the global phylogeographic structure of the entire family Moinidae.